Rapporteurs report of the first regular plenary meeting of the Latin American Shipping Commission - COLTRAM - SELA. Consejo Latinoamericano. Reunion Ordinaria, 12 Caracas; 1986 ([Caracas] SELA, 1986)
Programa basico de la Comision Latinoamericana de Transporte Maritimo (COLTRAM) para 1986-87.
Keywords: COOPERACION REGIONAL; TRANSPORTE MARITIMO